A new species of Falsocaenia Pic, 1922 from Amazonian Rainforest (Coleoptera: Lycidae) with an updated key to the species - Ferreira, Vinicius S. (Zootaxa, 2016)
While searching for Calochromini (Coleoptera: Lycidae) specimens in entomological collections and identifying other Lycidae, a new species of Falsocaenia Pic, 1922 was found in the collection of Instituto Nacional de Pesquisas da Amazônia (INPA). This genus is one of the smallest in the tribe Calopterini with 13 known species, two of which were recently described by Bocákova et al. (2012) in their revision of the genus, and can be found in Central and South America.